Fetal intrauterine whole body linoleic, arachidonic and docosahexaenoic acid contents and accretion rates - Kuipers, Remko S.; Luxwolda, Martine F.; Offringa, Pieter J.; Rudi Boersma, E.; Dijck-Brouwer, D.A. Janneke; Muskiet, Frits A.J. (Prostaglandins, leukotrienes and essential fatty acids, 2012)
There is no information on the whole body fatty acid (FA) contents of preterm or term infants, although scattered information on the FA-composition of many organs is available. We collected data on the weights, lipid contents and FA-compositions of the quantitatively most important fetal organs of appropriate for gestational age (AGA) Western infants. From these we estimated the total body contents of linoleic (LA), arachidonic (AA) and docosahexaenoic (DHA) acids at 25, 35 and 40 weeks of gestation. Western infants accrete FA in the order of LA>AA>DHA at all stages during pregnancy and the highest accretion rates are reached in the last 5 weeks of gestation, i.e. 342 mg LA, 95 mg AA and 42 mg DHA/day. At term, most of the infant's LA, AA and DHA is located in adipose tissue (68, 44 and 50%, respectively), with substantial amounts of LA also located in skeletal muscle (17%) and skin (13%); of AA in skeletal muscle (40%) and brain (11%); and of DHA in brain (23%) and skeletal muscle (21%). The term AGA infant has accreted about 21 g LA, 7.5 g AA and 3 g DHA, which constitutes a gap of 12 g LA, 3.3 g AA and 1.5 g DHA compared to a 35 weeks old AGA infant. The current fetal LA, AA and DHA pool sizes and accretion rates may especially be useful to estimate the preterm infant's requirements and the maternal LCP needs during pregnancy. Since they derive from populations with typically Western diets they do not necessarily reflect ‘optimality’ or ‘health’.